2021
DOI: 10.1128/msystems.01342-20
|View full text |Cite
|
Sign up to set email alerts
|

Genomes of Gut Bacteria from Nasonia Wasps Shed Light on Phylosymbiosis and Microbe-Assisted Hybrid Breakdown

Abstract: Phylosymbiosis is a cross-system trend whereby microbial community relationships recapitulate the host phylogeny. In Nasonia parasitoid wasps, phylosymbiosis occurs throughout development, is distinguishable between sexes, and benefits host development and survival. Moreover, the microbiome shifts in hybrids as a rare Proteus bacterium in the microbiome becomes dominant. The larval hybrids then catastrophically succumb to bacterium-assisted lethality and reproductive isolation between the species. Two importan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 133 publications
1
9
0
Order By: Relevance
“…Each of the HMT-352 strains shared a majority of its genome with all other studied HMT-352 strains, with approximately 70% of the genes in each genome being core to all HMT-352 strains. This proportion is similar to that of other studied bacterial species, although the proportion can vary substantially based on both the number of genome representatives and the degree of gene flow ( 37 39 ). However, despite the predicted homology for such large portions of the genome, the nucleotide sequences of the homologous regions differed substantially, resulting in ANI values between 93% and 95%.…”
Section: Discussionsupporting
confidence: 80%
“…Each of the HMT-352 strains shared a majority of its genome with all other studied HMT-352 strains, with approximately 70% of the genes in each genome being core to all HMT-352 strains. This proportion is similar to that of other studied bacterial species, although the proportion can vary substantially based on both the number of genome representatives and the degree of gene flow ( 37 39 ). However, despite the predicted homology for such large portions of the genome, the nucleotide sequences of the homologous regions differed substantially, resulting in ANI values between 93% and 95%.…”
Section: Discussionsupporting
confidence: 80%
“…melanogaster [ 41 ] and in the guts and external environment of D . melanogaster [ 42 , 43 ] but they have also been found in various other insects such as medicinal maggots [ 44 ], stable flies [ 45 ], Mexican fruit flies [ 46 ], house flies [ 47 ], mediterranean fruit fly [ 48 ], Nasonia wasps [ 49 ], black soldier fly [ 50 ], olive fly [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, transplanting interspecific microbial communities in Peromyscus deer mice significantly decreased their ability to digest food, and Nasonia wasps that received transplants of microbial communities from different wasp species had lower survival rate than those given their own microbiota ( Brooks et al, 2016 ). In Nasonia parasitoid wasps, the microbiome shifts in hybrids, as a rare Proteus bacteria become dominant, so the larval hybrids then catastrophically succumb to bacterium-assisted lethality and reproductive isolation between the species ( Cross et al, 2021 ). All these data showed that host characteristics could regulate microbial communities, and changes in the microbial communities were involved in host hybridization lethality, which reflected a mutually restrictive coevolutionary relationship between the hosts and associated microbiota.…”
Section: Discussionmentioning
confidence: 99%